2016
DOI: 10.1186/s40729-016-0041-7
|View full text |Cite
|
Sign up to set email alerts
|

Dental implants in patients treated with antiresorptive medication – a systematic literature review

Abstract: ObjectiveBisphosphonate-associated osteonecrosis of the jaws (BP-ONJ) is triggered by inflammatory processes. Typical trigger factors are periodontal disease, denture pressure sores, and surgical interventions such as tooth extractions. Unfortunately there is only little data on how to proceed with implant therapy in patients with bisphosphonate treatment. This topic is not addressed in the German guidelines on medication-associated osteonecrosis. Therefore a systematic literature review was performed.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 54 publications
4
58
0
11
Order By: Relevance
“…Indeed, in this systematic review, the literature search included terms about peri-implantitis, but only a handful of publications fulfilled the inclusion criteria. These observations are in accordance with information presented in recent systematic reviews and position papers on MRONJ (Aljohani et al, 2017;Ruggiero et al, 2014;Walter et al, 2016). Nevertheless, in the latter study, a small fraction of the evaluated implants (i.e., 6%) had three threads exposed, and considering the fact that the implants in this study were one-piece tissue level implants, one may question the validity of the findings/reporting in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, in this systematic review, the literature search included terms about peri-implantitis, but only a handful of publications fulfilled the inclusion criteria. These observations are in accordance with information presented in recent systematic reviews and position papers on MRONJ (Aljohani et al, 2017;Ruggiero et al, 2014;Walter et al, 2016). Nevertheless, in the latter study, a small fraction of the evaluated implants (i.e., 6%) had three threads exposed, and considering the fact that the implants in this study were one-piece tissue level implants, one may question the validity of the findings/reporting in this study.…”
Section: Discussionsupporting
confidence: 89%
“…In this context, the current review used a much wider search term basis compared to previous systematic reviews on this topic (e.g., Ata-Ali et al, 2016;Chrcanovic et al, 2016;Walter et al, 2016), both regarding implant therapy-related terms and ARDs; in particular, the search strategy included terms related to bone augmentation procedures and periimplant biological complications, as well as ARDs that have either been abandoned or not widely used, among other reasons due to systemic side effects (e.g., HRT and SrR has been associated with an increase in cardiovascular problems), or are still under development (e.g., CatK inhibitor and antisclerostin antibody) in order to obtain a comprehensive view of the field. It would otherwise be expected that many more studies-even in the form of case reports fulfilling the inclusion criteria (i.e., reporting on ≥ 10 cases)-would have been published and identified by the current systematic review, at least as it regards the long-standing BPs.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical challenge posed by implant failure risk, as influenced by the class of medication, is shown by the findings of a systematic review of 50 publications that contained little information to summarize statistically . Another review, which included 15 studies and 1339 patients, reported that the data were inconclusive, as no pooled estimate was provided because of the lack of long‐term follow‐up data.…”
Section: Discussionmentioning
confidence: 99%
“…When oral hygiene maintenance is at an adequate level, marginal bone loss is probably comparable to that observed in healthy controls (Tallarico et al., ). Finally, peri‐operative antibiotic prophylaxis is strongly recommended in patients on antiresorptive drugs and bone augmentation surgery should be avoided when possible (Walter et al., ). In summary, with precautions dental implant treatment is feasible in patients using oral administration of antiresorptive drugs.…”
Section: Bone Diseasesmentioning
confidence: 99%